2015
DOI: 10.1080/00958972.2015.1073270
|View full text |Cite
|
Sign up to set email alerts
|

Iron(IV) or iron(V)? Heterolytic or free radical? Oxidation pathways of a TAML activator in acetonitrile at −40 °C

Abstract: The oxidation of TAML complex(1) by various oxidants is explored in MeCN with 0.2% water at -40 °C where the iron(V)oxo complex is stable enough for reliable spectral identification. The iron(V)oxo state is achieved by using NaClO even faster than in the case of previously explored m-chloroperoxybenzoic acid. In contrast, H 2 O 2 and organic peroxides (benzoyl peroxide, tert-butylperoxide and tert-butylhydroperoxide)all convert 1 into the corresponding diiron(IV)-μ-oxo dimer (2) under the same conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…16 The advantages of using NaClO over m CPBA as an oxidant include higher reactivity and unlimited solubility in water. Figure 1 shows the spectra of 3 and the products formed in the presence of NaClO at pH 10.6 and 13.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16 The advantages of using NaClO over m CPBA as an oxidant include higher reactivity and unlimited solubility in water. Figure 1 shows the spectra of 3 and the products formed in the presence of NaClO at pH 10.6 and 13.…”
mentioning
confidence: 99%
“…We have recently reported that at −40 °C in MeCN iron(III) TAML 1 is oxidized into the iron(V)oxo species by NaClO and mCPBA though H 2 O 2 and organic peroxides convert 1 into the diiron(IV)(μ-oxo) dimer. 16 The advantages of using NaClO over mCPBA as an oxidant include higher reactivity and unlimited solubility in water. Figure 1 shows the spectra of 3 and the products formed in the presence of NaClO at pH 10.6 and 13.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[Fe V (bTAML)(O)] À was quantitatively generated by adding one equivalent of m-CPBA to a solution of the iron(III) precursor in CH 3 CN. [24] Alternative synthetic routes include the use of NaOCl as oxygen atom donor [25] and CH 3 CN : H 2 O (up to 90 %) as solvent mixture. [26] Photochemical [27] or electrochemical synthetic protocols [28] have also been reported.…”
Section: Oxoiron(v) Species With Tetraamido Macrocyclic Ligands (Taml's)mentioning
confidence: 99%
“…We have long known that TAML activators catalyze hypochlorite reactions . NaClO activates TAML catalysts to give Fe V O complexes from −40 °C to room temperature, highlighting a similarity with the most reactive intermediates in TAML/H 2 O 2 systems …”
Section: Introductionmentioning
confidence: 99%